PENGARUH WORK-LIFE BALANCE TERHADAP TURNOVER INTENTION DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL MODERATOR PADA KARYAWAN GENERASI Z - Chyntia Rahma Wandasari; Cholicul Hadi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This study aims to determine whether work-life balance has an influence on turnover intention with emotional intelligence as a moderator variable in generation Z employees. This is motivated by the high turnover rate in generation Z, especially in Indonesia. This research is a descriptive quantitative study followed by 58 generation Z employees in Indonesia aged 18-24 years and currently working. The measuring instrument used to measure Turnover Intention (TIS-6 Scale), Work-life Balance (WLB Scale), Emotional Intelligence (AES Scale). The analysis technique used is moderation analysis with the Jamovi 2.3.28.0 application for Mac. This study found that (1) work-life balance has a significant negative effect on turnover intention, (2) emotional intelligence has a significant positive effect on turnover intention. (3) emotional intelligence is not proven to moderate the effect of work-life balance on turnover intention in generation Z employees.